Collecting Comparative Data on Farmworker Housing and Health: Recommendations for Collecting Housing and Health Data Across Places and Time. (November 2015) - Arcury, Thomas A.; Gabbard, Susan; Bell, Bryan; Casanova, Vanessa; Flocks, Joan D.; Swanberg, Jennifer E.; Wiggins, Melinda F.
The substandard nature of the housing in which most farmworkers live has detrimental effects on their health, as well as on their children's health and development. However, little research has directly documented associations between farmworker housing and health; existing research is not always comparable due to differences in design and measurement. Comparative data can help determine actual causal links between housing characteristics and farmworker health and help to evaluate the efficacy of current housing policy. The goal of this paper is to provide guidelines promoting comparable research on farmworker housing and the association of this housing with health. This paper reviews general concepts relevant to measuring farmworker housing and health, issues that should be considered in designing farmworker housing and health research, data collection methods, and measures. It concludes with recommendations for a research agenda on farmworker housing and health.